Intervention in the framework of specific learning: a research-action - Sandra Teixeira Reis; Ana Luísa Vicente; Zélia Caçador Anastácio; Sofía Nobre; Florencio Vicente Castro (INFAD, 2019)
The aim of this paper is to report an intervention about the phonological processing near a 9-year-old child who attended the 4th year of primary school, in a group of schools in the central region of Portugal during the school year 2018/2019. The choice for this object of study was based on a case study carried out by the specialized professionals of this group of schools, after the child has been signaled by the class professor who indicate a possible “dyslexia”, due to difficulties revealed during the lessons, namely in reading and writing. In order to start the evaluation in this case study, we applied instruments for data collection related to qualitative methodology, namely interview, family drawing test, material consultation, exploratory proof of specific dyslexia (EPSD), realization of copying, dictation and error-raising. Instruments related to quantitative methodology were also used: Proof of Word recognition; Test Trail Making – Subtest of the neuropsychological assessment battery of Coimbra (NABC); Raven progressive matrices; Wechsler Intelligence Scale (WISC-III); reading comprehension test. From the results of the evaluation, it was found that the student presented an intellectual quotient – Brilliant Normal Intelligence (High Medium). However, phonological difficulties were evidenced (exchanges, omissions and additions). Given the evaluation results, an intervention plan was outlined that aimed at achieving the objectives defined in order to optimize the student’s capacities. We concluded that in order to achieve the success it is imperative that there be involvement among all the participants in the education of the child (school, parents, pupils, teachers, specialized technicians) and that it needs to be permanently a teamwork.